At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Make [tex]$r$[/tex] the subject of [tex]$m=\sqrt{\frac{6a + r}{5r}}$[/tex].

Sagot :

To make [tex]\( r \)[/tex] the subject of the equation [tex]\( m = \sqrt{\frac{6a + r}{5r}} \)[/tex], follow these steps:

1. Square both sides of the equation to eliminate the square root:
[tex]\[ m^2 = \left(\sqrt{\frac{6a + r}{5r}}\right)^2 \][/tex]
This simplifies to:
[tex]\[ m^2 = \frac{6a + r}{5r} \][/tex]

2. Multiply both sides by [tex]\( 5r \)[/tex] to clear the fraction:
[tex]\[ 5r \cdot m^2 = 6a + r \][/tex]
This can be written as:
[tex]\[ 5m^2r = 6a + r \][/tex]

3. Rearrange the equation to collect all terms involving [tex]\( r \)[/tex] on one side:
[tex]\[ 5m^2r - r = 6a \][/tex]

4. Factor out the common [tex]\( r \)[/tex] on the left-hand side:
[tex]\[ r(5m^2 - 1) = 6a \][/tex]

5. Solve for [tex]\( r \)[/tex] by dividing both sides by [tex]\( 5m^2 - 1 \)[/tex]:
[tex]\[ r = \frac{6a}{5m^2 - 1} \][/tex]

Thus, the expression for [tex]\( r \)[/tex] in terms of [tex]\( m \)[/tex] and [tex]\( a \)[/tex] is:
[tex]\[ r = \frac{6a}{5m^2 - 1} \][/tex]